Pattern of Malocclusion in Patients Seeking Orthodontic Treatment at Medical Colleges & Teaching Hospitals of Chitwan, Nepal - Pandey, Bashu Raj; Singh, Shailendra Kumar; Singh, Rajan; Mishra, Rajeev; Mishra, Srijana; Ghart, Bimala (Orthodontic Journal of Nepal, 2018)
Introduction: Various forms of malocclusion is most common dentofacial abnormality found in human population. People seek tteatment for such abnormalities based on the severity. The objective of this research is to evaluate Pattern of Malocclusion in Patients Seeking Orthodontic Treatment at Medical Colleges and Teaching Hospitals of Chitwan, Nepal. Materials & Method: Two hundred thirty nine pre-operative study casts of orthodontic patients aged from 12-50 years selected from 550 patient’s records of departments of orthodontics of Chitwan Medical Colleges and Colleges of Medical Sciences, Bharatpur of Chitwan. Standard protocol of Angle’s classification of malocclusion was used to classify malocclusion and its attributes were recorded. Pearson’s Chi square test was performed to justify the result. Result: The prevalence of malocclusion were 61.92% , 33.47% and 4.60% for Angle’s class I, Angle’s class II and Angle’s class III malocclusion respectively. Among various attributes of malocclusion, deep bite had highest frequency with 67.36% followed by overjet 58.99%, crowding 53.13% and spacing 35.98%, Anterior cross bite 11.71% reverse overjet 4.6%, posterior cross bite 1.2% and scissor bite 0.041%. Pearson Chi square test showed no relation among these attributes and sex and age at p < .05. Conclusion: Angle’s class I malocclusion is most prevalent followed by Angle’s class II and Angle’s class III.